ANALISIS PENGARUH JAM OPERASI BERBEDA TERHADAP KUALITAS PELUMAS TELLUS 32 PADA HEADSTOCK MESIN BUBUT DoALL LT 13 - Ichchan Adjury Essarofy; Ariyanto Ariyanto; Indra Feriadi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
Analysis of the Effect of Different Operating Hours on The Quality of Tellus 32 Lubricants On The Headstock of DoALL LT 13 Lathes is required to determine the interval of lubricant replacement time and to determine the effect of operating hours on the quality of Tellus 32 lubricants on the headstock of doall lt 13 lathes. Lubricant is a material (usually liquid) that serves to reduce wear between two surfaces of moving objects that rub against each other. The more hours of operation, the viscosity will also increase. This is due to the shifting force of the lubricant while the machine is operating. From the results of research and analysis of linear regression for lubricant replacement is based on viscosity . This for longer lubricant replacement if, compared to the manual book lathe DoALL LT13.